2014
DOI: 10.1186/2041-9139-5-1
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative atlas of Even-skipped and Hunchback expression in Clogmia albipunctata (Diptera: Psychodidae) blastoderm embryos

Abstract: BackgroundComparative studies of developmental processes are one of the main approaches to evolutionary developmental biology (evo-devo). Over recent years, there has been a shift of focus from the comparative study of particular regulatory genes to the level of whole gene networks. Reverse-engineering methods can be used to computationally reconstitute and analyze the function and dynamics of such networks. These methods require quantitative spatio-temporal expression data for model fitting. Obtaining such da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 62 publications
4
46
1
Order By: Relevance
“…Thus, the architecture of the definite CNS in Nemertea is congruent with the hypothetical ancestral spiralian pattern that consists of an anterior brain and paired, unsegmented, possibly lateral nerve cords [7,51]. The occurrence of a transitory caudal neuron in Nemertea supports the recently proposed hypothesis that posterior, possibly transitory neurons is an ancestral trait in the development of nervous systems in Spiralia (see discussion in [48]). A trochophore type larva has been postulated in the last common ancestor of Spiralia (in the sense of [1,52]) [2,4,53,54].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Thus, the architecture of the definite CNS in Nemertea is congruent with the hypothetical ancestral spiralian pattern that consists of an anterior brain and paired, unsegmented, possibly lateral nerve cords [7,51]. The occurrence of a transitory caudal neuron in Nemertea supports the recently proposed hypothesis that posterior, possibly transitory neurons is an ancestral trait in the development of nervous systems in Spiralia (see discussion in [48]). A trochophore type larva has been postulated in the last common ancestor of Spiralia (in the sense of [1,52]) [2,4,53,54].…”
Section: Discussionsupporting
confidence: 73%
“…As outlined above, however, these subapical neurons are not part of the developing definite nervous system [15,18]. In various mollusk species, similar invaginations have been shown to give rise to the cerebral ganglia [4345], also without displaying immuoreactivity against the respective antibodies [4648]. While the hypothesis that the fronto-lateral epidermal invaginations represent the primordia of the brain-ring seems to be supported by published information, it is challenged by the fact that at least RFa-lir neurons of the brain likely originate from more dorsally located parts of the frontal epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with the situation in the chelicerate, myriapod and insect embryos, in which hunchback mRNA is typically localised anteriorly or in an anterior-to-posterior gradient along the early embryo (Tautz and Pfeifle 1989;Schwager et al 2009;Janssen et al 2011;Chang et al 2013;Duncan et al 2013;Crombach et al 2014;Janssens et al 2014). Moreover, our results provide no evidence for hunchback expression in a group of mesenchymal cells, which would correspond to the cumulus of the chelicerate embryo (Schwager et al 2009).…”
Section: No Indication Of Maternal or "Gap Gene"-like Expression Of Hcontrasting
confidence: 85%
“…It has been shown that hunchback has multiple roles during development of protostome species including maternally mediated anterior patterning, body segmentation as well as patterning of neural and mesodermal tissues (Lehmann and Nüsslein-Volhard 1987;Isshiki et al 2001;Pinnell et al 2006). While the maternal expression of hunchback is shared by a number of arthropod and annelid species, including insects (Drosophila and other dipterans), spiders, myriapods, leeches and polychaetes (Tautz and Pfeifle 1989;Savage and Shankland 1996;Werbrock et al 2001;Schwager et al 2009;Janssen et al 2011;Janssens et al …”
Section: Introductionmentioning
confidence: 99%
“…C. alpipunctata has been used as a model in descriptive molecular embryology since the mid 1990's [56,[64][65][66][67][68][69][70][71]. Embryonic transcriptome data and a staging scheme for embryos are also available [59,61]…”
mentioning
confidence: 99%